Anisotropy in the Viscoelastic Response of Knee Meniscus Cartilage. Issue 1 (26th January 2017) - Coluccino, Luca; Peres, Chiara; Gottardi, Riccardo; Bianchini, Paolo; Diaspro, Alberto; Ceseracciu, Luca
Background: The knee meniscus is instrumental to stability, shock absorption, load transmission and stress distribution within the knee joint. Such functions are mechanically demanding, and replacement constructs used in meniscus repair often fail because of a poor match with the surrounding tissue. This study focused on the native structure–mechanics relationships and on their anisotropic behavior in meniscus, to define the target biomechanical viscoelastic properties required by scaffolds upon loading. Methods: To show regional orientation of the collagen fibers and their viscoelastic behavior, bovine lateral menisci were characterized by second harmonic generation microscopy and through time-dependent mechanical tests. Furthermore, their dynamic viscoelastic response was analyzed over a wide range of frequencies. Results and conclusions: Multilevel characterization aims to expand the biomimetic approach from the structure itself, to include the mechanical characteristics that give the meniscus its peculiar properties, thus providing tools for the design of novel, effective scaffolds. An example of modeling of anisotropic open-cell porous material tailored to fulfill the measured requirements is presented, leading to a definition of additional parameters for a better understanding of the load transmission mechanism and for better scaffold functionality.